Comparative life cycle assessment of swarf cleaning methods for sustainable manufacturing - Karadimas, Georgios; Pagone, Emanuele; Salonitis, Konstantinos (Elsevier, 2025)
The metal manufacturing industry faces significant environmental challenges due to high energy consumption and waste production. This study critically analyzes two advanced swarf cleaning methods including supercritical CO2 cleaning and Cryoclean to evaluate their environmental impacts. Using Life Cycle Assessment (LCA), the research compares these methods to determine their effectiveness in reducing CO2 emissions and overall environmental impact. The results reveal that Cryoclean is the preferred method, slightly outperforming supercritical CO2 cleaning in minimizing carbon emissions and ecosystem damage. This makes Cryoclean the more sustainable option for most industrial applications requiring effective, residue-free cleaning. Specifically, Cryoclean reduced CO2 emissions by approximately 5% compared to supercritical CO2 cleaning. The study also highlights the energy and resource efficiency of these methods, emphasizing their role in promoting sustainable manufacturing practices. By providing a detailed comparison of these cleaning processes, the study offers valuable insights into optimizing swarf recycling, thereby supporting the global shift towards more sustainable industrial practices. This research underscores the importance of adopting efficient swarf cleaning technologies to enhance the sustainability of metal manufacturing and meet environmental targets.
Keywords: 4014 Manufacturing engineering; Swarf Cleaning; Supercritical CO2; Cryoclean; Life Cycle Assessment